STUDY OF SOCIAL CULTURAL ENVIRONMENTAL PHENOMENOLOGY ON CREDIT DECISION MAKING AT BANK CENTRAL ASIA TBK OFFICE REGION II SEMARANG - Fransiska Intan Kumalasari; I Made Bayu Dirgantara (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this study is to examine and analyze the influence given by reference groups that can have an impact on credit decision making of prospective debtors at BCA Kanwil II Semarang, examine and analyze the influence of family can have an impact on credit decisions of prospective debtors at BCA Kanwil II Semarang, examine and analyze the impact of proximity to bank officers on debtor credit decision making at BCA Kanwil II Semarang, examine and analyze the impact of advances in banking technology on debtor credit decision making at BCA Kanwil II Semarang. This type of qualitative research was chosen by researchers to get a better understanding of the influence of credit decision making at Bank BCA Regional Office II. This study will use a phenomenological approach. This approach is in accordance with the focus of the problem, questions and research objectives of this study. The subjects that will be used in this study are customers who have loans at Bank Central Asia, Tbk Regional Office II Semarang. ` Keywords: Group Reference, Family Influence, Closeness to Bank Officers, Impact of Technological Advances, Credit Decision Making